MARKET BASKET ANALYSIS MENGGUNAKAN ALGORITMA HASH BASED PADA DATA PENJUALAN DI O2 SWALAYAN - Fenesia Yunika, Fenesia Yunika (STMIK KAPUTAMA, 2024)
O2 Supermarkets have stock of goods available in the warehouse. During this time there is a buildup of goods in the warehouse because there is no system to analyze transaction data so that losses occur. Therefore, a system is needed to manage these goods in order to reduce stocks of goods that are not selling well and make stocks of goods that sell well in warehouses through consumer spending patterns. To analyze data on consumer spending patterns, the Market Basket Analysis Method can be used. This method can be used to analyze consumer spending patterns. The algorithm used is the Hash Based and Association Rule Algorithm because it can overcome the determination of frequent itemsets from k-itemset candidates with a large number and speed up information on consumer spending patterns. With existing data and using this algorithm it can produce a lot of information. The results of this study get 6 Rules with a minimum Confidence of 50% and minimum Support>= 4. From consumer spending patterns that can be used as a strategy to support sales, knowing which items are selling best, placing goods so that they are more efficient in picking up the goods desired by consumers, not only shopping patterns but also more controlled stock of goods.